The EFFECT OF GIVING SPINACH LEAF PUDDING (AMARANTHUS HYBRIDUS) PREVENTING CALCIUM DEFICIENCY AND IRON DEFICIENCY ANEMIA - Ummy Maisarah Rasyidah; Anita Dahliana; Winnie Nirmala Santosa (Medika Alkhairaat : Jurnal Penelitian Kedokteran dan Kesehatan, 2023)
Background: Growing rapidly during adolescence increases a person's need for nutrients. Anemia is more common among adolescent girls. The dietary needs during adolescence are also very high due to the peak bone mass (PBM) that lasts throughout this period. This study aimed to determine whether adolescent girls who consumed spinach (Amaranthus Hybridus) would have increased levels of hemoglobin and blood calcium. Methods: Pre- and post-testing was used in one group of quantitative research employing a time series experiment in a quasi-experimental design to assess the intervention's effects. January 2022 study was conducted. 30 young ladies from Surabaya took part in the study. A method of deliberate sampling was used to collect samples. Data collection was done from primary sources and examined using the statistical paired sample t-test. Result: After consuming spinach pudding, blood calcium and hemoglobin levels increased. Shapiro-Wilk Test was normal and significantly different (p<0.05) hemoglobin and calcium levels before and after consuming spinach pudding from paired sample test results. Conclusion: Before and after receiving spinach pudding, there is a considerable difference in the blood hemoglobin and calcium levels.